Classifying the Magnetosheath Behind the Quasi‐Parallel and Quasi‐Perpendicular Bow Shock by Local Measurements. Issue 9 (19th September 2021) - Karlsson, T.; Raptis, S.; Trollvik, H.; Nilsson, H.
Abstract: We investigate and evaluate the possibility of using local magnetosheath measurements to classify the plasma according to upstream conditions. In order to do this, we use simultaneous measurements from the Cluster spacecraft from time intervals when one of them is located in the solar wind, and the other in the magnetosheath. In particular, we study the classification of the magnetosheath plasma into the classes quasi‐parallel versus quasi‐perpendicular and foreshock/no foreshock (referring to the geometry of the upstream bow shock). We evaluate this method based on the magnetosheath measurements of the high‐energy ion energy flux, magnetic field standard deviation, and ion temperature anisotropy. We find that the method is promising and useful, in that it eliminates the uncertainties associated with propagating upstream measurements made far from the bow shock. Finally, we discuss some possible extensions of the methodology to be investigated in the future. Key Points: We use Cluster multipoint measurements to investigate the different magnetosheath plasma environments according to the upstream conditions Local magnetosheath measurements can be used to characterize and classify the magnetosheath plasma with respect to upstream conditions We suggest future extensions to the methodology